Copper increases reductive dehalogenation of haloacetamides by zero-valent iron in drinking water: Reduction efficiency and integrated toxicity risk. (15th December 2016) - Chu, Wenhai; Li, Xin; Bond, Tom; Gao, Naiyun; Bin, Xu; Wang, Qiongfang; Ding, Shunke
Abstract: The haloacetamides (HAcAms), an emerging class of nitrogen-containing disinfection byproducts (N-DBPs), are highly cytotoxic and genotoxic, and typically occur in treated drinking waters at low μg/L concentrations. Since many drinking distribution and storage systems contain unlined cast iron and copper pipes, reactions of HAcAms with zero-valent iron (ZVI) and metallic copper (Cu) may play a role in determining their fate. Moreover, ZVI and/or Cu are potentially effective HAcAm treatment technologies in drinking water supply and storage systems. This study reports that ZVI alone reduces trichloroacetamide (TCAcAm) to sequentially form dichloroacetamide (DCAcAm) and then monochloroacetamide (MCAcAm), whereas Cu alone does not impact HAcAm concentrations. The addition of Cu to ZVI significantly improved the removal of HAcAms, relative to ZVI alone. TCAcAm and their reduction products (DCAcAm and MCAcAm) were all decreased to below detection limits at a molar ratio of ZVI/Cu of 1:1 after 24 h reaction (ZVI/TCAcAm = 0.18 M/5.30 μM). TCAcAm reduction increased with the decreasing pH from 8.0 to 5.0, but values from an integrated toxic risk assessment were minimised at pH 7.0, due to limited removal MCAcAm under weak acid conditions (pH = 5.0 and 6.0). Higher temperatures (40 °C) promoted the reductive dehalogenation of HAcAms. Bromine was preferentially removed over chlorine, thus brominated HAcAms were more easily reduced than chlorinated HAcAms by ZVI/Cu. Although tribromoacetamide was more easily reduced than TCAcAm during ZVI/Cu reduction, treatment of tribromoacetamide resulted in a higher integrated toxicity risk than TCAcAm, due to the formation of monobromoacetamide (MBAcAm). Graphical abstract: Highlights: ZVI reduces HAcAms via sequential dechlorination, whereas Cu does not. The addition of Cu to ZVI (ZVI/Cu) significantly enhances reduction of HAcAms. Lower pH increases TCAcAm removal, but the MCAcAm formed increases toxicity. Bromine is preferentially removed over chlorine in HAcAms by ZVI/Cu. Reduction of TBAcAm causes higher toxicity than of TCAcAm, due to MBAcAm formation.